123k views
3 votes
PLEASE HELP!!!!!!!!!!!!!!!!!!

PLEASE HELP!!!!!!!!!!!!!!!!!!-example-1
User Johndodo
by
5.4k points

1 Answer

3 votes

Answer:

The solution to the system of equations be:


y=-3,\:x=2

Explanation:

Given the system of equations


\begin{bmatrix}y=3x-9\\ y=-2x+1\end{bmatrix}

Let us solve the system by the elimination method


\begin{bmatrix}y=3x-9\\ y=-2x+1\end{bmatrix}

Arrange equation variables for elimination


\begin{bmatrix}y-3x=-9\\ y+2x=1\end{bmatrix}

subtracting the equations


y+2x=1


-


\underline{y-3x=-9}


5x=10

so the system of equations becomes


\begin{bmatrix}y-3x=-9\\ 5x=10\end{bmatrix}

solve 5x for x


5x=10

Divide both sides by 5


(5x)/(5)=(10)/(5)


x = 2


\mathrm{For\:}y-3x=-9\mathrm{\:plug\:in\:}x=2


y-3\cdot \:2=-9


y-6=-9

Add 6 to both sides


y-6+6=-9+6


y=-3

Therefore, the solution to the system of equations be:


y=-3,\:x=2

User Jwillmer
by
5.9k points